Deliberation and Identity Rules: The Effect of Anonymity, Pseudonyms and Real-Name Requirements on the Cognitive Complexity of Online News Comments. (February 2021) - Moore, Alfred; Fredheim, Rolf; Wyss, Dominik; Beste, Simon
How do identity rules influence online deliberation? We address this question by drawing on a data set of 45 million comments on news articles on the Huffington Post from January 2013 to May 2015. At the beginning of this period, the site allowed commenting under what we call non-durable pseudonyms. In December 2013, Huffington Post moved to regulate its forum by requiring users to authenticate their accounts. And in June 2014, Huffington Post outsourced commenting to Facebook altogether, approximating a 'real-name' environment. We find a significant increase in the cognitive complexity of comments (a proxy for one aspect of deliberative quality) during the middle phase, followed by a decrease following the shift to real-name commenting through Facebook. Our findings challenge the terms of the apparently simple trade-off between the goods and bads of anonymous and real-name environments and point to the potential value of durable pseudonymity in the context of online discussion.